1999
DOI: 10.1177/095968019952003
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Relations and Protection of the Environment: Research Findings from a New Policy Field

Abstract: Since 1991 a research group has investigated the relationship between environmental policies and the industrial relations systems in 10 European countries. It might be expected that the growing importance of the environment as a policy issue would prompt an enlargement of the traditional agenda of industrial relations systems, leading to stronger inclusion of the social partners in environmental action; but in the main, evidence of such enlargement has been sparse. The Netherlands, where works councils legisla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…There is no prima facie reason why the content of trade unionism could not be extended to environmental concerns and solidarities; however, Gregory et al . (: 159) note that new agendas must often compete with older, more pressing ones and Dufour and Hege () argue that new agendas too distant from core concerns are unlikely to achieve renewal. Thus, in terms of recruiting new members and activists the issues seem to be how important is the environment to existing and prospective members and can an active, collective identity coalesce around it?…”
Section: Situating the Article Within The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…There is no prima facie reason why the content of trade unionism could not be extended to environmental concerns and solidarities; however, Gregory et al . (: 159) note that new agendas must often compete with older, more pressing ones and Dufour and Hege () argue that new agendas too distant from core concerns are unlikely to achieve renewal. Thus, in terms of recruiting new members and activists the issues seem to be how important is the environment to existing and prospective members and can an active, collective identity coalesce around it?…”
Section: Situating the Article Within The Literaturementioning
confidence: 99%
“…For example, Gregory et al . (: 152–9) found that most European unions’ environmental roles at company level, whilst providing them with information rights, cast them as trouble‐shooters rather than strategic partners.…”
Section: Situating the Article Within The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Die über die Auswirkungen der Globalisierung entstandene Verbindungslinie zwischen Umweltthemen und Gewerkschaften (vgl. ILO 2002;Gregory et al 1999) manifestierte sich auch in Österreich an Kampagnen wie "STOP-GATS" oder der "Sozialforumsbewegung".…”
Section: Die Historische Arbeiterinnenbewegung Und Umweltfragenunclassified
“…Therefore, the labour movement changed its strategy towards the environment, seeing opportunities in environmental improvements as possibilities to ensure long-term employment interests. The labour movement also wanted to use the environmental agenda in the development of the members' working conditions and strengthen the prevention of health risks at the workplace level (Gregory et al, 2001). Furthermore, trade unions' new orientation towards sustainability provided an opportunity for the movement to strengthen its societal engagement and to maintain the movement as an organization with a project for societal change.…”
Section: The Trade Union Movement and Sustainabilitymentioning
confidence: 99%